Effect of Pocket Height on Aluminum flow through zero-bearing extrusion dies to produce single solid profile using FEM Simulation: تأثير ارتفاع المغذي على تدفق الألمنيوم عبر قوالب البثق ذات سطح الضبط الصفري لإنتاج مقطع مصمت مفرد بطريقة العناصر المنتهية - Mohammad Majed Altaleb, Almohannad Makki (Journal of engineering sciences and information technology, 2020)
Extrusion is known as an industrial forming process for producing long sections with a fixed cross-sectional area and is often used to extrude colored metals, especially aluminum. The aluminum rods (Billets) are heated and pressed through a die to obtain the required profile. The research aims to study the effect of Pocket height when using zero bearing dies by modeling using the INSPIRE EXTRUDE METAL program package for a single rectangular section of 65 mm in length and 1.5 mm in width, and then to conduct experimental verification of the results by designing, manufacturing and testing a real mold in an aluminum extrusion factory that matches one of the molds Studied. As we studied a group of molds that have a Pocket so that the height of the pocket in them changes from zero (a reference flat die) to a height of 20 mm. The feeder design takes into account the homogenization of the flow across the studied section, which narrows in the center and widens at the edges. The measurement of the relative flow velocity at the front of the section was used as an indicator to analyze the results of the analytical experiment. The study showed that a certain height of the feeder of 10 mm must be maintained for the studied section. The FEM results and the practical experience were identical. This shows the importance of the FEM and its effectiveness in shortening the experimental work and that it can, to a large extent, save time and effort to manufacture, test and correct dies.